Για το βιβλίο: Konstantinos Kalantzis (2019). Tradition in the Frame. Photography, Power, and Imagination in Sfakia, Crete. Μπλούμιγκτον, Ιντ.: Indiana University Press, 321 σελ. ISBN 978-0253-03712-1 - Bakalaki, Alexandra (The Greek Review of Social Research, 2021)
Ν/Α